The effects of hip- vs. knee-dominant hamstring exercise on biceps femoris morphology, strength, and sprint performance: a randomized intervention trial protocol - Scott K. Crawford; Jack Hickey; Jessica Vlisides; Jennifer S. Chambers; Samuel J. Mosiman; Bryan C. Heiderscheit (BMC, 2023)
Abstract Background The hamstrings are an important muscle group that contribute to horizontal force during sprint acceleration and are also the most injured muscle group in running-based sports. Given the significant time loss associated with hamstrings injury and impaired sprinting performance following return to sport, identifying exercises that drive adaptations that are both protective of strain injury and beneficial to sprint performance is important for the strength and conditioning professional. This paper describes the study protocol investigating the effects of a 6-week training program using either the hip-dominant Romanian deadlift (RDL) or the knee-dominant Nordic hamstring exercise (NHE) on hamstring strain injury risk factors and sprint performance. Methods A permuted block randomized (1:1 allocation) intervention trial will be conducted involving young, physically-active men and women. A target sample size of 32 will be recruited and enrolled participants will undergo baseline testing involving extended-field-of-view ultrasound imaging and shear wave elastography of the biceps femoris long head muscle, maximal hamstrings strength testing in both the RDL and NHE, and on-field sprint performance and biomechanics. Participants will complete the 6-week training intervention using either the RDL or NHE, according to group allocation. Baseline testing will be repeated at the end of the 6-week intervention followed by 2 weeks of detraining and a final testing session. The primary outcome will be regional changes in fascicle length with secondary outcomes including pennation angle, muscle cross sectional area, hamstring strength, and maximal sprint performance and biomechanics. An exploratory aim will determine changes in shear wave velocity. Discussion Despite extensive research showing the benefits of the NHE on reducing hamstring strain injury risk, alternative exercises, such as the RDL, may offer similar or potentially even greater benefits. The findings of this study will aim to inform future researchers and practitioners investigating alternatives to the NHE, such as the RDL, in terms of their effectiveness in reducing rates of hamstring strain injury in larger scale prospective intervention studies. Trial Registration The trial is prospectively registered on ClinicalTrials.gov (NCT05455346; July 15, 2022).